Obtaining and characterization of a composite with polymer matrix and corn cob waste filler (Research, Society and Development, 2020)
It was studied the feasibility of using corn cob to obtain a polymer composite. It was used of the corn cob in Three-grain sizes, and some formulations of the composite of polyester resin and powders were used, and the most appropriate formulation was chosen. For the characterization of the composite thermal and mechanical properties were determined. The main advantage of the composite was the low density, about 1.06 kg/m³ for the thick powder formulation. The composite presented an inferior mechanical behavior concerning the resin for all the studied particle sizes and formulations. The composite presented better mechanicals results for the bending strength, reaching 25.3 MPa for the thick powder formulation. The composite also proved itself to be viable for thermal applications since it has average thermal conductivity inferior to 0.21 W/m, being classified as thermal insulation and can be used to manufacture structures that do not require significant mechanical strength, such as tables, chairs, benches, panels, works of art, crafts and solar prototypes, such as ovens and stoves.